VD_FINDINFO Pron / 2013 / 52 vom 19. Februar 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, DÉLAI DE RECOURS, DÉCISION D'IRRECEVABILITÉ | 309 let. a CPC (CH), 319 let. a CPC (CH), 321 al. 2 CPC (CH)